Maternal-fetal attachment among pregnant women at risk for mental health: a comparative study - Barut, Sümeyye; Baransel, Esra Sabancı (National Scientific Medical Center, 2024)
Background: Mental problems (stress, anxiety, and depression) experienced by the pregnant negatively affect the life and health of the fetus in the future and may increase the complications seen in pregnancy, delivery and postpartum. Aim: In this study, it was aimed to determine maternal-fetal attachment among pregnant women at risk for mental health. Methods: This cross-sectional study was conducted with 404 women between June 10, 2023 and September 30, 2023 in the obstetrics and gynecology outpatient clinics of a private hospital in eastern Türkiye. Data were collected with the Personal Information Form, the Maternal Antenatal Attachment Scale (MAAS), and the General Health Questionnaire (GHQ-28). The data were evaluated according to the General Health Questionnaire (GHQ-28) mean score, by dividing them into two groups as those at risk for mental health and those without risk for mental health. Results: The MAAS mean score of the women participating in the study was 67.78±9.66, and the mean scores of the subscales of "Attachment Quality" and "Time Spent on Attachment" of the MAAS were 40.82±55.33 and 26.95±5.62, respectively; it was determined that the mean score they got from the GHQ-28 was 2.98±3.81. Between the groups with high-risk and non-risky pregnancies, the mean scores of the MAAS and the subscale of Attachment Quality were found to be higher in non-risky pregnancies (p<0.05). Additionally, it was determined that the mean score of “Time Spent on Attachment” of non-risky pregnant women was higher than that of high-risk pregnant women, but there was no statistically significant difference between the groups (p> 0.05). The GHQ-28 mean score was lower in non-risky pregnant women (p<0.05). Conclusion: In the study, it was determined that the maternal-fetal attachment levels of pregnant women with psychological risk were low. Therefore, the results suggest that it is necessary to determine mental problems in pregnant women and to conduct screening programs more frequently. © 2024, National Scientific Medical Center. All rights reserved.
Keywords: Attachment; maternal; mental health; pregnant